Gene frequencies of D16S539, D7S820 and D13S317 STRs alleles in random malay population - S., Panneerchelvam; Norazmi, Mohd Nor (Pusat Pengajian Sains Kesihata, Universiti Sains Malaysia, 2003)
DNA analysis of biological materials for individualization purposes has become the norm In crime investigation. A number of different DNA markers exist for individualization of biological stains. However STR based DNA profiling(microsatellite polymorphism) is the most widely used technique in personal identification. Personal identification tests involve mathematical probabilities of genetic markers to ascertain the likelihood of probability for a conclusive answer. In this study distribution of allele frequencies of three STR polymorphic genetic markers-viz .,D13S317,D7S820 and 0168539 were studied in random malay population of Malaysia. The observed genotypic distribution showed no significant deviation from Hardy-weinberg equilibrium . The data in the present study have been compared with recently published data as reported in the liuterature for various population groups. The data on the three validated STRs will be useful in parentage testing and personal identification in criminal and immigration cases.